Тетразоло[1,5-с]хіназолін-(6Н)-5-они(тіони): синтез, функціоналізація, фізико-хімічні та біологічні властивості - Антипенко, Олексій Миколайович; Antypenko, O. M. (Запорізький державний медичний університет, 2016)
В дисертаційній роботі вирішена поетапна стратегія цілеспрямованого пошуку біологічно активних речовин, що об’єднує підходи препаративної органічної хімії з методологією in silico, in vitro та in vivo фармакологічних досліджень, у межах якої синтезовано ряд заміщених тетразоло[1,5-с]хіназолінів, калій 7-R-8-R1-9-R2-тетразоло[1,5-с]хіназолін-5-тіолатів та відповідних тіонів, 5-алкіл-(алкарилетіл)тіотетразоло[1,5-с]хіназолінів, N,N-діалкіл-2-(тетразоло-[1,5-с]хіназолін-5-ілтіо)алкіламінів, (тетразоло[1,5-с]хіназолін-5-ілтіо)-етанонів-(етанолів), (тетразоло[1,5-с]хіназолін-5-ілтіо)карбонових кислот та естерів, (тетразоло[1,5-с]хіназолін-5-ілтіо)ацетамідів, заміщених тетразоло[1,5-с]-хіназолін-5(6H)-онів, 6-алкіл(фенетіл)-тетразоло[1,5-с]хіназолін-5(6H)-онів, 2-(5-оксотетразоло[1,5-с]хіназолін-6(5H)-іл)карбонових кислот та їх естерів, N-арил-(бензил-)-2-[(5-оксотетразоло[1,5-с]хіназолін-6(5H)-іл]ацетамідів та 1-(2-(1Н-тетразоло-5-іл)-R1-феніл)-3-R2-феніл(етил)сечовин. Обговорено та доведено можливості та умови їх синтетичної модифікації, досліджено фізико-хімічні, спектральні та біологічні властивості. В процесі виконання роботи синтезовано 168 сполук (158 вперше), серед яких знайдені речовини з високою протипухлинною, протимікробною, актопротекторною та гіпоглікемічною активністю, рекомендовано «сполуки-лідери» для подальших досліджень, а також виявлені закономірності зв’язку між хімічною будовою та фармакологічною активністю. The thesis is devoted to the biologically active substances among tetrazolо[1,5-c]-quinazoline(6H)-5-ones(thiones) and their functional derivatives, evaluation of their physico-, chemical and biological properties, structure–activity relationship and recommendations of the most active compounds for further pharmacological testing. Hydrolytic cleavage of substituted tetrazolo[1,5-c]quinazoline was studied and it was shown, that appropriate 2-(1H-tetrazol-5-yl)anilines were the products of mentioned reaction. It was established, that reaction was implemented in stages, through appropriate intermediates – substituted N-(2-(1H-tetrazol-5-yl)phenyl)formamides, which were extracted in some cases. Potassium tetrazolo[1,5-c]quinazoline-(6H)-5-thiolates and related thiones were synthesized for the first time based on the [5+1]-cyclocondensation of substituted 2-(1H-tetrazol-5-yl)anilines with carbon disulfide or its synthetic equivalent – potassium xanthogenate. Potassium salts were used for alkylation reaction by halogenoalkanes, halogenoalcohols, halogenophenacyls, carboxylic acids and their esters. Alkylation of potassium tetrazolo[1,5-c]quinazoline-(6H)-5-thiolates with proper N-R-2-chloroacetamides enabled to obtain a number of N-R-2-[tetrazolo-[1,5-c]quinazolin-5-yl)thio]acetamides. Also, the possibility of their synthesis was shown through in situ generated imidazolide of 2-[tetrazolo[1,5-c]quinazoline-5-yl)thio]acetic acid. Interaction of 2-(1H-tetrazol-5-yl)anilines with ethyl(phenyl)isocyanates was studied and it was found, that in case of room temperature and medium of acetic acid 1-(2-(1H-tetrazol-5-yl)phenyl-R1)-3-R2-phenyl(ethyl)ureas were produced, while in case of refluxing – tetrazolo[1,5-c]quinazoline-(6H)-5-ones were formed. To synthesize the latter one, a number of alternative methods were developed, namely the interaction of 2-(1H-tetrazol-5-yl)anilines with N,N'-carbonyldiimidazole or ethylchloroformiate. Peculiarities of tetrazolo[1,5-c]quinazoline(6H)-5-ones alkylation with halogen containing compounds were established, and the possibilities and limitations of corresponding 2-[(5-oxotetrazolo[1,5-c]quinazoline-6(5H)-yl]acetic acids, their esters and amides formation were shown by this approach. During the studies 168 compounds (158 for the first time) were synthesized. Their spectral properties (1H and 13C NMR, UV-, IR-, LC-, MS-(EI) – spectra, and elemental analysis data) were established and S- and N-alkylation regioselectivity was confirmed. Combinatorial library was built of the previously unknown bioactive substances with bioluminescence inhibition, antibacterial, antitumor, hypoglycemic, actoprotective and antihypoxic activities and toxicity data. It was found, that the most of compounds have a negative influence on the bioluminescence of bacteria P. leiognathi Sh1 in acute and chronic tests, showing toxicity. Thus the highest toxicity had 4-nitro-2-((tetrazolo[1,5-c]quinazoline-5-ylthio)methyl)phenol- (7.2), 1-phenyl- (8.1), 1-(4-methylphenyl)- (8.2), 1-(4-ethoxyphenyl)-(8.3) and (2,5-dimethoxyphenyl)-2-(tetrazolo[1,5-c]quinazoline-5-ylthio)-ethanone (8.4). The results of molecular docking with the epidermal growth factor receptor and protein CK2 kinase serves as explanation of the proposed mechanism of antitumor activity, and with γ-PPAR, HSD11B1 and DPP4 enzyme – for hypoglycemic activity. The structural similarity, in silico screening and pharmacological studies have identified a new class of compounds with hypoglycemic activity of substances 13 and 14. Compounds 14.4, 14.21 and 13.1 showed high activity in models of dexamethasone diabetes, and in some cases exceeded activity of Metformin and Gliclazide. It was found, that N-aryl(benzyl, heteryl)-2-(tetrazolo[1,5-c]quinazoline-5-thio)acetamides (12.34-12.36) were selective against the cell line LOX IMVI of melanoma, while 2-(tetrazolo[1,5-c]quinazoline-5-ylthio)-1-(p-tolyl)-ethanone (8.2) and carboxylic acids 9.2, 9.3 were selective against the cell line CCRF-SEM of leukemia. To establish the likely mechanism of action, acetamides 12.29, 12.35, 12.36 were tested with protein kinase CK2. Thus, the most active compound was 12.35 with LD50 = 4.9 μM. Furthermore, QSAR models of cancer cell lines growth’s inhibition were established for RPMI-8226, SR, NCI-H226, NST-15, KM12, OVCAR-3, ACHN and T-47D lines for tetrazolo[1,5-c]quinazoline-(6H)-5-ones(thiones), which along with molecular docking results to the enzyme CK2 formed the base for further studies of the antitumor activity mechanisms. Analyzing the results of pharmacological screening, structure–activity relationship the «lead compounds» were selected. They were suggested for further research and were classified as Class IV by acute toxicity.
Tetrazolо[1,5-c]quinazoline(6H)-5-ones(thiones): synthesis, functionalization, physico-chemical and biological properties
Keywords: синтез; 2-(1Н-тетразоло-5-іл)аніліни; тетразоло[1,5-с]- хіназолін-5(6Н)-они(тіони); спектральні характеристики; фармакологічні дослідження; протеїнкіназа; synthesis; 2-(1H-tetrazol-5-yl)anilines; tetrazolо[1,5-c]- quinazoline(6H)-5-ones(thiones); spectral characteristics; pharmacological studies; protein kinase